Lattice Distortion in Hollow Multi‐Shelled Structures for Efficient Visible‐Light CO2 Reduction with a SnS2/SnO2 Junction. Issue 2 (13th November 2019) - You, Feifei; Wan, Jiawei; Qi, Jian; Mao, Dan; Yang, Nailiang; Zhang, Qinghua; Gu, Lin; Wang, Dan
Abstract: Precise control of the micro‐/nanostructures of nanomaterials, such as hollow multi‐shelled structures (HoMSs), has shown its great advantages in various applications. Now, the crystal structure of building blocks of HoMSs are controlled by introducing the lattice distortion in HoMSs, for the first time. The lattice distortion located at the nanoscale interface of SnS2 /SnO2 can provide additional active sites, which not only provide the catalytic activity under visible light but also improve the separation of photoexcited electron–hole pairs. Combined with the efficient light utilization, the natural advantage of HoMSs, a record catalytic activity was achieved in solid–gas system for CO2 reduction, with an excellent stability and 100 % CO selectivity without using any sensitizers or noble metals. Abstract : Lattice distortion was introduced into hollow multi‐shelled structures by using SnS2 /SnO2 as a building block, which successfully converted CO2 into CO with an excellent activity, 100 % selectivity, and a long‐term stability.